2017
DOI: 10.3390/beverages3030030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additional Information on Consumer Acceptance: An Example with Pomegranate Juice and Green Tea Blends

Abstract: Pomegranate Juice (PJ) and Green Tea (GT) products have increased in popularity because of their beneficial health properties. Consumers look for healthier beverages, and rely on labels, claims, and product packaging when choosing a product. The objectives of this study were to determine (1) the sensory profiles and acceptance of PJ and GT blends;(2) whether additional information would have an effect on consumer acceptance; and (3) the total phenolic content (TPC) of the samples. Six PJ and GT blends were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…Making consumers aware of the nature of the jellies they were consuming made a difference, leading to higher scores for overall liking and the satisfaction degree for most of the evaluated attributes (appearance, pomegranate ID, sourness, hardness, solubility, and adhesiveness). A recent study found similar results, with the overall liking of pomegranate-based drinks increasing after information which was described previously in the Materials and Methods section was provided to the consumers [47]. Figure 1 represents a correlation mapping of consumer overall liking with the descriptive attributes (only statistically significant ones were used) to determine the drivers of liking.…”
Section: Descriptive Sensory Analysis Consumer Acceptability and Driving Sensory Attributessupporting
confidence: 66%
“…Making consumers aware of the nature of the jellies they were consuming made a difference, leading to higher scores for overall liking and the satisfaction degree for most of the evaluated attributes (appearance, pomegranate ID, sourness, hardness, solubility, and adhesiveness). A recent study found similar results, with the overall liking of pomegranate-based drinks increasing after information which was described previously in the Materials and Methods section was provided to the consumers [47]. Figure 1 represents a correlation mapping of consumer overall liking with the descriptive attributes (only statistically significant ones were used) to determine the drivers of liking.…”
Section: Descriptive Sensory Analysis Consumer Acceptability and Driving Sensory Attributessupporting
confidence: 66%
“…Contrary to the present findings, previous research highlighted an increase in hedonic responses in real tasting conditions compared with those in blind conditions. It was reported that information about the positive health effects of antioxidant components increased liking for pomegranate and green tea juices [19], unfamiliar fruit juice made with açaí [16], and juice made with different types of exotic tropical fruits (camu-camu, açaí, cajà, and umbo) [18]. The effect of information about winemaking byproduct ingredients (grape skin) on consumers' liking was also found to have a positive effect when used for tea infusion [62].…”
Section: Consumer Responses To the New Developed Food Samplesmentioning
confidence: 99%
“…Product information about positive health effects has been reported to be highly influential in affecting consumers' expectations [16][17][18][19]. However, this information is not always enough to lead consumers to accept and consume new food products.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptualizations have been sorted into three broad categories: emotional, abstract, and functional (Thomson et al, 2010). Due to the fact that extrinsic factors affect consumer conceptualization and expectations, several studies have asked participants to evaluate samples with their extrinsic factors present, instead of a blind tasting (Choi & Lee, 2019; Higa, Koppel, & Chambers, 2017; Spinelli, Masi, Zoboli, Prescott, & Monteleone, 2015). As found by Spinelli et al (2015), consumer acceptability and emotional response can be affected by the mismatch between the intrinsic and extrinsic evaluation by visual packaging.…”
Section: Introductionmentioning
confidence: 99%